The 2016 National Matriculation and General Certificate of Secondary Education English Test: a Challenge to the Goal of Foreign Languages Education in Vietnamese Schools - Van, Hoang Van (VNU Journal of Science: Education Research; Vol 33 No 4, 2017)
Every year in Vietnam there are nearly a million Vietnamese 12 graders taking as compulsory the national general certificate of secondary education English testto be eligible to receive  general certificate of secondary school education. Since 2015, the English test has been used for students to achieve two goals: (1) to receive general certificate of secondary school education and (2) to gain entrance to Vietnamese universities and colleges. The test is referred to as “the national matriculation and general certificate of secondary education English test”. It has a clear format, clearly specified contents, a clear and detailed scoring scheme, and is made public in the Vietnamese mass media. However, looked at from both theoretical and practical levels, there are still problems with the test that need to be examined and discussed. This is the purpose of this paper. As a way of start, the paper will provide a description of the test. Then, it will examine some of its key qualities, and present its washback and impact on the Vietnamese general school foreign language education. In the conclusion, after summarizing the strengths and weaknesses of the test, the paper will conclude that due to its weaknesses in both content and format,and its long-term negative washback, the 2016 national matriculation and general certificate of secondary education English test presents a big challenge to the communication goal of the Vietnamese general foreign language education. The paper recommends that for the quality of foreign language teaching and learning in Vietnamese schools to be improved andfor the foreign language education in Vietnamese schools to meet the requirements of globalization in Vietnam, a radical renovation in both test format and test administration should be exercised.